Kikuchi-Fujimoto disease presenting with prolonged fever and aseptic meningitis in a child: a case report - Li, Panying; Yang, Jing; Mao, Li; Huang, Li; Ni, Qian (Frontiers in Pediatrics, 2025)
Kikuchi-Fujimoto Disease (KFD) is a rare, self-limiting lymphadenitis that predominantly affects young women of Asian descent and is less frequently encountered in children. The disease is characterized by focal and indurated cervical lymphadenopathy with fever and other infrequent systemic manifestations, including neurologic symptoms that are rare. This report details the diagnosis and treatment of a 14-year-old male with an atypical case of KFD. He exhibited a fever that persisted for over 1 month together with dizziness, nausea, arthralgia, night sweats, weight loss, and splenomegaly. On day 16 following fever onset, he presented with symptoms of aseptic meningitis, with symptoms of cervical lymph node swelling and pain only manifesting on day 25 after fever onset. Positron emission tomography (18F-FDG PET/CT) revealed the enlargement of lymph nodes in several regions of the body. After considering a diagnosis of lymphoma, KFD was ultimately diagnosed via cervical lymph node biopsy. His condition improved following oral prednisone administration. This case report highlights the complex disease course of KFD and the difficulties associated with diagnosing it at an early stage. KFD is rarely considered in the differential diagnosis for children with prolonged unexplained fever, especially with delayed lymphadenopathy, leading to potential misdiagnosis and unnecessary investigations.